Innovative method for quantification of cell-cell adhesion in 96-well plates - Zepeda-Moreno, Abraham; Hoffmann, Isabel; Hellwig, Isabelle; Hoang, Thanh Van; Pietsch, Larissa; Lakshmanan, Vinoth Kumar; Wagner, Wolfgang; Ho, Anthony Dick (Cell adhesion & migration, 2011)
Cell adhesion is an important part of many complex biological processes. It plays crucial roles in cancer, development, and maintenance of stem cell compartment. The measurement of adhesion under experimental conditions might provide important information for cell biology. There are several protocols to measure adhesion, usually based on washing or shaking to remove non-adherent cells. Here, we describe a quantification method based on gravitational force to measure adhesion in a 96-well format. Non-adherent cells are separated and only vital cells are quantified with a colorimetric assay. As example we provide the quantification of cell-cell interaction with blocking function antibodies for CD44, an N-cadherin antagonists and the stromal cell derived factor-1 alpha (SDF-1). This method facilitates fast and reliable measurement of cell adhesion in multiwell format for screening assays.
Gesehen am 22.12.2022